The feasibility of oral targeted drug delivery: Gut immune to particulates? - Yuehong Ren; Wei Wu; Xingwang Zhang (Elsevier, 2023)
Targeted drug delivery is constantly updated with a better understanding of the physiological and pathological features of various diseases. Depending on high safety, good compliance and many other undeniable advantages, attempts have been undertaken to complete an intravenous-to-oral conversion of targeted drug delivery. However, oral delivery of particulates to systemic circulation is highly challenging due to the biochemical aggressivity and immune exclusion in the gut that restrain absorption and access to the bloodstream. Little is known about the feasibility of targeted drug delivery via oral administration (oral targeting) to a remote site beyond the gastrointestinal tract. To this end, this review proactively contributes to a special dissection on the feasibility of oral targeting. We discussed the theoretical basis of oral targeting, the biological barriers of absorption, the in vivo fate and transport mechanisms of drug vehicles, and the effect of structural evolution of vehicles on oral targeting as well. At last, a feasibility analysis on oral targeting was performed based on the integration of currently available information. The innate defense of intestinal epithelium does not allow influx of more particulates into the peripheral blood through enterocytes. Therefore, limited evidence and lacking exact quantification of systemically exposed particles fail to support much success with oral targeting. Nevertheless, the lymphatic pathway may serve as a potentially alternative portal of peroral particles into the remote target sites via M-cell uptake.